Differences of reactive oxygen species metabolism in top, middle and bottom part of epicarp and mesocarp influence tomato fruit cracking. Issue 6 (1st November 2020) - Zhang, Chuan; Zhao, Yingjie; Jiang, Fangling; Wu, Zhen; Cui, Shouyao; Lv, Haimeng; Yu, Lu
ABSTRACT: Tomato ( Solanum lycopersicum L.) fruit cracking is a serious economic problem, affecting fruit quality and yield. During abiotic stress, the imbalance of reactive oxygen species (ROS) metabolism causing membrane damage might increase the susceptibility of pericarp to changing environment and then affect fruit cracking. To further validate the relationship between ROS metabolism and fruit cracking, we used cracking-resistant tomato 'LA1698' and cracking-susceptible tomato 'LA2683' as test materials. ROS, membrane lipid peroxidation, antioxidants and soluble protein in different parts (top, middle and bottom) of epicarp and mesocarp were studied. Results showed that, the highest ROS levels and membrane lipid peroxidation degree were observed in the top of epicarp in 'LA2683'. Moreover, 'LA2683' displayed lower superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR) activity and ascorbic acid (AsA) content, and maintained higher polyphenol oxidase (PPO), peroxidase (POD), catalase (CAT) activity and soluble protein content in each part of epicarp, compared with 'LA1698'. In conclusion, the top of epicarp in 'LA2683' accumulated higher ROS, concurrent with decreased ROS scavenging ability, and the disordered ROS homoeostasis led to cellular oxidative damage, which could effect the occurrence of cracking at the top of fruit. ROS metabolism in epicarp may play an important role in fruit cracking.